Whole Life Critical Factors Influencing Construction Project Performance for Different Objectives: Evidence from Thailand - Homthong, Samart; Moungnoi, Wutthipong; Charoenngam, Chotchai (Buildings (Basel), 2024)
This study aimed to identify the critical factors (CFs) influencing project performance and analyze their relative importance across multidimensional criteria throughout the project life cycle. Based on a literature review, 179 individual factors were categorized into nine performance criteria. A questionnaire survey was conducted with client representatives, consultants, and contractors in Thailand. The statistical analysis of 93 subjects showed that the significance levels of the performance criteria and CFs changed depending on the considered phase in the project’s life cycle. The analysis identified the three criteria (client satisfaction, quality, time) that were most frequently used to measure the success of a project. Furthermore, the findings revealed the top 10 CFs for each performance category throughout the life cycle. Notably, these findings provide compelling evidence of the following most important CFs across the performance measures: competence of project participants, adequate experience of project participants, the availability of competent staff, positive personal attitudes among project participants, participation in environmental initiatives by management, competent supervisors, effective project planning and control, the need for collaboration, and the professionalism of the project team’s services. This research provides insights into the factors that influence project success and have managerial implications for project stakeholders, facilitating informed decision making throughout the life cycle. Through establishing novel perspectives, this study enhances the knowledge base in the construction management domain.